2021
DOI: 10.3389/fpsyg.2021.695147
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric Properties of the Spanish Version of the Cognitive Emotional Regulation Difficulties Questionnaire (CERQ) in Higher Education Students in Times of Covid-19

Abstract: The Cognitive Emotion Regulation Questionnaire (CERQ) is an instrument developed to assess the cognitive strategies of emotional regulation used by people after experiencing a negative event. The present study aimed to validate the Spanish version of the CERQ in students of the University of Granada (Spain) during the Covid-19 homebound. An online scale was developed and applied based on the Spanish version of the CERQ-S36, consisting of 36 items structured around nine cognitive strategies. Using a mixed sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 67 publications
(79 reference statements)
0
4
0
2
Order By: Relevance
“…The CERQ is an emotion regulation assessment tool that allows discrimination between cognitive and behavioural strategies [ 33 ]. Prior studies have shown empirical evidence of the psychometric properties of the CERQ in the Spanish population [ 32 , 33 , 43 , 46 , 66 , 67 ]. However, less attention has been paid to its properties in the adolescent population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The CERQ is an emotion regulation assessment tool that allows discrimination between cognitive and behavioural strategies [ 33 ]. Prior studies have shown empirical evidence of the psychometric properties of the CERQ in the Spanish population [ 32 , 33 , 43 , 46 , 66 , 67 ]. However, less attention has been paid to its properties in the adolescent population.…”
Section: Discussionmentioning
confidence: 99%
“…This tool consists of 36 items distributed into nine subscales related to emotion regulation strategies. This questionnaire has shown to be reliable and valid in prior studies with both Spanish [ 32 , 43 ] and international populations [ 37 , 44 , 48 , 49 , 50 ].…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…El creciente interés científico por los procesos y las habilidades personales e interpersonales que facilitan la regulación emocional se ha hecho patente en el incremento de publicaciones en los últimos 30 años (Domínguez-Lara, 2017;Garnefski et al, 2002;Rodríguez-Sabiote et al, 2021). Esta proliferación de investigaciones ha puesto de relieve el importante papel que puede desempeñar la regulación emocional en la evaluación, tratamiento y prevención de diversos problemas salud mental.…”
Section: Figuraunclassified
“…El CERQ es instrumento de evaluación de la regulación emocional que permite discriminar entre estrategias cognitivas y conductuales (Carvajal et al, 2021). Estudios anteriores han demostrado evidencias empíricas sobre las propiedades psicométricas del CERQ en población española (Carvajal et al, 2021;Chamizo Nieto et al, 2020;Domínguez-Sánchez et al, 2011;Holgado-Tello et al, 2018;Orgilés et al, 2018;Rodríguez-Sabiote et al, 2021). Sin embargo, se ha prestado menos atención a sus propiedades en la población adolescente.…”
Section: Discusión Y Conclusionesunclassified